2017
DOI: 10.1002/adsc.201700327
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium–Benzyl Complexes Bearing Chiral Iminophosphonamide Ligands: Synthesis and Application in Catalytic Asymmetric Amine‐Silane Dehydrocoupling Reactions

Abstract: A series of novel iminophosphonamide ligands with chiral diamine moieties were designed and synthesized. Yttrium-benzyl compounds bearing these chiral iminophosphonamide ligands showed high reactivity and selectivity on the first catalytic asymmetric cross-dehydrogenative coupling of amines with prochiral silanes under mild conditions. A stable silylamine-boron derivative was synthesized in up to 23% ee, as determined by chiral HPLC analysis. By employing this catalyst system, catalytic kinetic resolution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…Many catalysts either enhance the nucleophilicity of the amine or the electrophilicity of silane, which allows significant variability in catalyst design. The production of chiral silylamines has recently emerged through catalysis [56] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many catalysts either enhance the nucleophilicity of the amine or the electrophilicity of silane, which allows significant variability in catalyst design. The production of chiral silylamines has recently emerged through catalysis [56] …”
Section: Discussionmentioning
confidence: 99%
“…Guan and Li used the yttrium‐benzyl complex ( 31 ) bearing a chiral iminophosphoamide for the rapid coupling of mixed aryl‐ and alkyl‐secondary silanes and simple amine substrates under ambient conditions to high conversions of 91–100 % (Figure 10). [56] …”
Section: F‐block Catalystsmentioning
confidence: 99%
“…However, the chemistry with chiral iminophosphonamide ligands is still nearly dormant. In 2007, racemic trans -1,2-diaminocyclohexyl-linked N -aryl bis(iminophosphonamines) and subsequent complexes with group 3 and group 13 elements were reported by Hill et al 13 More recently, Li and Guan reported on yttrium and alkaline earth metal complexes of chiral iminophosphonamides and their application as catalysts in cross-dehydrogenative coupling reactions of amines 14. In both reports, the chiral center was solely introduced at one nitrogen atom of the NPN ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Note that for the whole ligand class of iminophosphonamides only a few examples of alkaline earth metal complexes are known [7] . Moreover, only one heteroleptic calcium complex based on a chiral iminophosphonamide has been reported, with the chirality solely introduced at one nitrogen center [8] . None of these reported alkaline earth metal complexes based on iminophosphonamides showed PL.…”
Section: Introductionmentioning
confidence: 99%